The Influence Of School Principals’ Managerial Competence, Teachers’pedagogical Competence, And School Culture On The Quality Of Education - Listyaningrum, Asri Linda; Buchori, Achmad; Soedjono (AJIS: Academic Journal of Islamic Studies, 2025)
This study examines the influence of school principals' managerial competence, teachers' pedagogical competence, and school culture on the quality of education at SMP Negeri Sub Rayon 01, Jepara Regency. The approach used in this study is quantitative with a descriptive correlational design. Data were collected through questionnaires completed by 168 teachers, and data analysis was conducted using simple and multiple linear regression. The study results show that the managerial competence of school principals significantly influences the quality of education, accounting for 64.2%, with a strong influence category. Teachers' pedagogical competence affects the quality of education by 66.2%, also within the strong influence category. School culture affects the quality of education by 52.1%, with a moderate influence category. Additionally, these three variables simultaneously influence the quality of education by 62.7%, indicating a significant contribution from all three in improving the quality of education. These findings suggest that strengthening the competence of school principals, teachers' pedagogical competence, and school culture is crucial in creating a quality educational environment. Therefore, there is a need for integrated policies and development programs to improve these three aspects to achieve optimal educational quality.